Corticotropin-Releasing Factor-Producing Cells in the Paraventricular Nucleus of the Hypothalamus and Extended Amygdala Show Age-Dependent FOS and FOSB/DeltaFOSB Immunoreactivity in Acute and Chronic Stress Models in the Rat - Kovács, László Á.; Berta, Gergely; Csernus, Valér; Ujvári, Balázs; Füredi, Nóra; Gaszner, Balázs (Frontiers in Aging Neuroscience, 2019)
Corticotropin-releasing factor (CRF) immunoreactive (ir) neurons of the paraventricular nucleus of the hypothalamus (PVN) play pivotal role in the coordination of stress response. CRF-producing cells in the central nucleus of amygdala (CeA) and oval division of the bed nucleus of stria terminalis (BNSTov) are also involved in stress adaptation and mood control. Immediate early gene products, subunits of the transcription factor activator protein 1 (AP1) are commonly used as acute (FOS) and/or chronic (FOSB/deltaFOSB) markers for the neuronal activity in stress research. It is well known that the course of aging affects stress adaptation, but little is known about the aging-related stress sensitivity of CRF neurons. To the best of our knowledge, the stress-induced neuronal activity of CRF neurons in the course of aging in acute and chronic stress models was not studied systematically yet. Therefore, the aim of the present study was to quantify the acute restraint stress (ARS) and chronic variable mild stress (CVMS) evoked neuronal activity in CRF cells of the PVN, CeA and BNSTov using triple-label immunofluorescence throughout the whole lifespan in the rat. We hypothesized that the FOS and FOSB content of CRF cells upon ARS or CVMS decreases with age. Our results showed that the FOS and FOSB response to ARS declined with age in the PVN-CRF cells. BNSTov and CeA CRF cells did not show remarkable stress-induced elevation of these markers neither in ARS, nor in CVMS. Exposure to CVMS resulted in an age-independent significant increase of FOSB/∆FOSB immunosignal in PVN-CRF neurons. Unexpectedly, we detected a remarkable stress-independent FOSB/deltaFOSB signal in CeA- and BNSTov-CRF cells that declined with the course of aging. In summary, PVN-CRF cells show decreasing acute stress sensitivity (i.e. FOS and FOSB immunoreactivity) with the course of aging, while their (FOSB/deltaFOSB) responsivity to chronic challenge is maintained till senescence. Stress exposure does not affect the occurrence of the examined Fos gene products in CeA- and BNSTov-CRF cells remarkably suggesting that their contribution to stress adaptation response does not require AP1-controlled transcriptional changes.